Gradient anti-static wear-resistant coating and preparation method thereof

By constructing the nickel-based alloy bottom layer and gradient ceramic top layer on the substrate surface, the problem of the limited application of traditional anti-static coatings in high wear-resistant environments is solved, and efficient electrostatic retardation and wear resistance are achieved.

CN119506762APending Publication Date: 2025-02-25XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411681114.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing anti-static coatings are limited in application in high wear-resistant environments. The conductive filler content of traditional inorganic composite coatings needs to be strictly controlled, which is prone to problems such as untimely dissipation of electrostatic dissipation or excessively rapid damage to the substrate.

Method used

By using the preparation method of a gradient antistatic wear-resistant coating, the nickel-based alloy bottom layer and a gradient ceramic surface layer are constructed on the surface of the substrate, and the content of the doped phase is increased in sequence from the inside to the outside to form a conductive channel to divert the static charge.

Benefits of technology

It achieves uniform density and hardness of the coating structure, stable and excellent anti-static properties and wear resistance, avoids damage to the substrate by electrostatic action, and is suitable for surface strengthening of complex components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506762A_ABST
    Figure CN119506762A_ABST
Patent Text Reader

Abstract

The invention relates to the field of material surface treatment, in particular to a gradient anti-static wear-resistant coating and a preparation method thereof. The preparation method of the gradient anti-static wear-resistant coating comprises the following steps: roughening a base body, and carrying out first spraying on nickel-based alloy powder on the roughened surface of the base body to obtain a nickel-based alloy bottom layer; matching the powder corresponding to the main phase and the powder corresponding to the doping phase according to a preset proportion, and mechanically mixing to obtain mixed powder for preparing the gradient ceramic surface layer; and continuously carrying out second spraying of multiple layers of mixed powder on the surface of the nickel-based alloy bottom layer to obtain a gradient ceramic surface layer, so as to obtain the gradient anti-static wear-resistant coating consisting of the nickel-based alloy bottom layer and the gradient ceramic surface layer. The gradient anti-static wear-resistant coating prepared by the preparation method has the material properties of anti-static function and high wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material surface treatment, and in particular to a gradient antistatic wear-resistant coating and a preparation method thereof. Background Art

[0002] Static electricity is a common phenomenon of charging. In industrial production, people need to use static electricity to carry out certain activities, such as electrostatic dust removal, painting, mineral processing and printing, etc. On the other hand, they need to prevent the harm caused by static electricity, such as dust explosion caused by static electricity, static electricity sparks generated during the filling and transportation of flammable liquids, and static electricity sparks generated by friction and peeling of solid materials (such as rubber, plastic and synthetic fibers). When static electricity accumulates or sparks, if there is flammable liquid vapor, it is very easy to cause fire and explosion accidents.

[0003] In the fields of aerospace, petrochemical, electronics, semiconductor manufacturing, etc., in order to prevent serious explosion accidents caused by static electricity, necessary anti-static measures must be taken for the production, loading and unloading equipment and places of flammable and explosive materials, combustible dust, flammable gas and liquid. Preparing anti-static coating on the surface of materials is one of the effective ways to solve the problem of static explosion.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] The purpose of the present disclosure is to provide a gradient antistatic wear-resistant coating and a preparation method thereof, aiming to prepare a material coating with antistatic function and strong wear resistance.

[0006] Other features and advantages of the present disclosure will become apparent from the following detailed description, or may be learned in part by the practice of the present disclosure.

[0007] According to one aspect of an embodiment of the present disclosure, a method for preparing a gradient antistatic wear-resistant coating is provided, comprising: roughening a substrate, and performing a first spraying of a nickel-based alloy powder on the surface of the roughened substrate to obtain a nickel-based alloy bottom layer; mechanically mixing a main corresponding powder and a doping corresponding powder according to a preset ratio to obtain a mixed powder for preparing a gradient ceramic surface layer; continuously performing a second spraying of multiple layers of the mixed powder on the surface of the nickel-based alloy bottom layer to obtain a gradient ceramic surface layer, so as to obtain a gradient antistatic wear-resistant coating composed of the nickel-based alloy bottom layer and the gradient ceramic surface layer.

[0008] According to some embodiments of the present disclosure, based on the aforementioned scheme, the nickel-based alloy bottom layer is one of a nickel-cobalt-chromium-aluminum-yttrium coating, a nickel-chromium-aluminum-yttrium coating, a cobalt-chromium-aluminum-yttrium coating, a nickel-chromium coating, a nickel-chromium-aluminum coating, a nickel-clad aluminum coating, an aluminum-clad nickel coating, and an aluminum-clad nickel-chromium coating; the particle size range of the nickel-based alloy powder is 15 to 75 μm.

[0009] According to some embodiments of the present disclosure, based on the aforementioned scheme, the process parameters of the first spraying are: spraying power of 40-70 kW, main gas flow of 50-200 L / min, powder feeding rate of 15-30 g / min, and spraying distance of 8-15 cm.

[0010] According to some embodiments of the present disclosure, based on the above-mentioned scheme, the main phase is one or more of aluminum oxide, zirconium oxide, chromium oxide, yttrium oxide, and hafnium oxide, and the doped phase is one or more of titanium dioxide, silicon carbide, zirconium carbide, chromium carbide, titanium carbide, hafnium carbide, titanium diboride, and zirconium diboride; the mechanical mixing time is 2 to 10 hours, the particle size range of the main phase corresponding to the powder is 25 to 75 μm, and the particle size range of the doped phase corresponding to the powder is 15 to 75 μm.

[0011] According to some embodiments of the present disclosure, based on the aforementioned scheme, the process parameters of the second spraying are: spraying power is 50-100kW, main gas flow is 60-200L / min, powder feeding rate is 15-30g / min, and spraying distance is 8-15cm.

[0012] According to some embodiments of the present disclosure, based on the aforementioned scheme, the first spraying and the second spraying are both performed by plasma spraying, and the process parameters of the plasma spraying method are as follows: the scanning speed of the plasma generator is 1000-6000 mm / s, the time interval between two deposition cycles in the same coating is 5-60s, and the deposition interval time of each coating in the gradient ceramic surface layer is greater than or equal to 2 minutes.

[0013] According to the second aspect of the embodiment of the present disclosure, a gradient antistatic wear-resistant coating is provided, which is obtained by the preparation method of the gradient antistatic wear-resistant coating as mentioned above, and the gradient antistatic wear-resistant coating includes: a nickel-based alloy bottom layer and a gradient ceramic surface layer, and the gradient ceramic surface layer includes a main phase and a doped phase; the content of the doped phase increases from the inside to the outside, and the mass percentage of the doped phase is 2% to 50%.

[0014] According to some embodiments of the present disclosure, based on the aforementioned solution, the thickness of the nickel-based alloy bottom layer is 50-120 μm, and the porosity does not exceed 5%.

[0015] According to some embodiments of the present disclosure, based on the aforementioned solution, the thickness of the gradient ceramic surface layer does not exceed 500 μm, and the porosity does not exceed 5%.

[0016] According to some embodiments of the present disclosure, based on the above scheme, the surface resistance of the gradient antistatic wear-resistant coating is 10 6 ~10 8 Ω, bonding strength is greater than or equal to 30MPa, hardness is 900~1500HV 0.3 The average friction coefficient is 0.6~0.9, and the wear rate is (2.0~10.0)×10 -6 mm·N -1 ·m -1 .

[0017] The exemplary embodiments of the present disclosure may have some or all of the following beneficial effects:

[0018] In the technical solutions provided in some embodiments of the present disclosure, the spraying technology preparation process and the coating composition are coordinated and regulated to successfully construct a multifunctional gradient structured antistatic wear-resistant coating on the substrate surface. On the one hand, the coating has a uniform and dense structure, high hardness, and stable and excellent antistatic and wear resistance. The static electricity on the coating surface is slowly dissipated along the pathway formed by the conductive phase inside its gradient structure, avoiding damage to the substrate by static electricity, and effectively solving the application limitations of traditional organic coatings in highly wear-resistant and antistatic environments; on the other hand, the gradient structure design makes the interface between the coatings disappear, effectively relieves the interface stress, and enhances the coating's bonding strength and other properties; on the other hand, the coating has strong applicability and can achieve surface strengthening for complex components such as disks, shafts, boxes, thin-walled parts, and grooves, with good economic and social benefits.

[0019] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0021] Figure 1 A schematic diagram schematically shows a process flow diagram of a method for preparing a gradient antistatic wear-resistant coating in an exemplary embodiment of the present disclosure;

[0022] Figure 2 A schematic diagram of the structure of a gradient antistatic wear-resistant coating in an exemplary embodiment of the present disclosure is schematically shown;

[0023] Figure 3A macroscopic schematic diagram of a gradient antistatic wear-resistant coating in an exemplary embodiment of the present disclosure is schematically shown;

[0024] Figure 4 A schematic cross-sectional view of a gradient antistatic wear-resistant coating prepared in exemplary embodiment 1 of the present disclosure is schematically shown;

[0025] Figure 5 A schematic diagram schematically shows the antistatic performance of the gradient antistatic wear-resistant coating prepared in exemplary embodiment 1 of the present disclosure;

[0026] Figure 6 The variation curve of the friction coefficient of the gradient antistatic wear-resistant coating prepared in exemplary embodiment 1 of the present disclosure is schematically shown. DETAILED DESCRIPTION

[0027] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more comprehensive and complete and will fully convey the concept of the example embodiments to those skilled in the art.

[0028] In addition, the described features, structures or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced without one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known methods, devices, implementations or operations are not shown or described in detail to avoid blurring the various aspects of the present disclosure.

[0029] The block diagrams shown in the accompanying drawings are merely functional entities and do not necessarily correspond to physically independent entities. That is, these functional entities may be implemented in software form, or in one or more hardware modules or integrated circuits, or in different networks and / or processor devices and / or microcontroller devices.

[0030] The flowcharts shown in the accompanying drawings are only exemplary and do not necessarily include all the contents and operations / steps, nor must they be executed in the order described. For example, some operations / steps can be decomposed, and some operations / steps can be combined or partially combined, so the actual execution order may change according to actual conditions.

[0031] Static electricity is a common phenomenon of charging. In industrial production, people need to use static electricity to carry out certain activities, such as electrostatic dust removal, painting, mineral processing and printing, etc. On the other hand, they need to prevent the harm caused by static electricity, such as dust explosion caused by static electricity, static electricity sparks generated during the filling and transportation of flammable liquids, and static electricity sparks generated by friction and peeling of solid materials (such as rubber, plastic and synthetic fibers). When static electricity accumulates or sparks, if there is flammable liquid vapor, it is very easy to cause fire and explosion accidents.

[0032] In the fields of aerospace, petrochemical, electronics industry, semiconductor manufacturing, etc., in order to prevent serious explosion accidents caused by static electricity, necessary anti-static measures must be taken for the production, loading and unloading equipment and places of flammable and explosive materials, combustible dust, flammable gases and liquids.

[0033] Preparing antistatic coating on the surface of materials for the production, loading and unloading and transportation of flammable and explosive goods is one of the effective methods to solve the problem of static explosion. It is generally believed that when the surface resistance of the material is 10 6 ~10 8 When Ω, the coating achieves an anti-static effect.

[0034] There are two types of commonly used antistatic coatings. One is to add certain antistatic agents or conductive substances to the organic coating, such as carbon black, graphene, silver, copper, nickel, aluminum and other powders; the other is a multifunctional inorganic coating. However, in the face of a high wear-resistant antistatic environment, such as a transmission shaft used for spinning cotton and spinning, it is difficult for organic antistatic coatings to achieve long-term stable service. Among inorganic materials, oxide ceramics such as aluminum oxide and chromium oxide have the characteristics of high hardness, good wear resistance and antioxidant ability, but their resistivity is extremely high and cannot play an antistatic effect. Conductive fillers such as titanium dioxide and tin oxide must be added to them. The heterogeneous phase inside the traditional inorganic composite coating is dispersed, and the content of the conductive filler needs to be strictly controlled. There are problems such as untimely electrostatic dissipation, excessively fast electrostatic dissipation that damages the substrate, and poor wear resistance of the material. Therefore, it is urgent to design and develop a new type of antistatic wear-resistant coating.

[0035] In order to avoid the shortcomings of the prior art, the present invention provides a gradient antistatic wear-resistant coating and a preparation method thereof, which can enable the conductive particles to form a continuous conductive channel in the ceramic coating, effectively diverting the static charge accumulation on the surface of the material, while the gradient structure reduces the stress concentration inside the coating and improves the comprehensive mechanical properties of the material. In addition, the preparation process of the method is safe and controllable, which solves the problem that the performance of the existing coating is difficult to control, and has good economic and social benefits.

[0036] The implementation details of the technical solution of the embodiment of the present disclosure are elaborated in detail below.

[0037] Figure 1The following is a schematic diagram of a method for preparing a gradient antistatic wear-resistant coating in an exemplary embodiment of the present disclosure. Figure 1 As shown, the preparation method of the gradient antistatic wear-resistant coating includes steps S101 to S103:

[0038] Step S101, roughening the substrate, and first spraying nickel-based alloy powder on the roughened substrate surface to obtain a nickel-based alloy bottom layer;

[0039] Step S102, mixing the main powder and the doping powder according to a preset ratio and then mechanically mixing them to obtain a mixed powder for preparing a gradient ceramic surface layer;

[0040] Step S103, continuously performing a second spraying of multiple layers of the mixed powder on the surface of the nickel-based alloy bottom layer to obtain a gradient ceramic surface layer, so as to obtain a gradient antistatic wear-resistant coating composed of the nickel-based alloy bottom layer and the gradient ceramic surface layer.

[0041] In the technical solutions provided in some embodiments of the present disclosure, the spraying technology preparation process and the coating composition are coordinated and regulated to successfully construct a multifunctional gradient structured antistatic wear-resistant coating on the substrate surface. On the one hand, the coating has a uniform and dense structure, high hardness, and stable and excellent antistatic and wear resistance. The static electricity on the coating surface is slowly dissipated along the pathway formed by the conductive phase inside its gradient structure, avoiding damage to the substrate by static electricity, and effectively solving the application limitations of traditional organic coatings in highly wear-resistant and antistatic environments; on the other hand, the gradient structure design makes the interface between the coatings disappear, effectively relieves the interface stress, and enhances the coating's bonding strength and other properties; on the other hand, the coating has strong applicability and can achieve surface strengthening for complex components such as disks, shafts, boxes, thin-walled parts, and grooves, with good economic and social benefits.

[0042] Below, each step of the method for forming a gradient antistatic wear-resistant coating in this exemplary embodiment will be described in more detail with reference to the accompanying drawings and examples.

[0043] In step S101, the substrate is roughened, and a nickel-based alloy powder is first sprayed on the surface of the roughened substrate to obtain a nickel-based alloy bottom layer.

[0044] Specifically, the substrate can be first cleaned and dried for standby use, and then the dried substrate is placed in a sandblasting machine for roughening treatment, and then the sand on the surface of the substrate is cleaned with compressed air, and then the nickel-based alloy bottom layer is prepared on the roughened substrate surface by plasma spraying.

[0045] In one embodiment of the present disclosure, the nickel-based alloy bottom layer is one of nickel-cobalt-chromium-aluminum-yttrium coating, nickel-chromium-aluminum-yttrium coating, cobalt-chromium-aluminum-yttrium coating, nickel-chromium coating, nickel-chromium-aluminum coating, nickel-clad aluminum coating, aluminum-clad nickel coating, and aluminum-clad nickel-chromium coating; the particle size range of the nickel-based alloy powder is 15 to 75 μm.

[0046] In one embodiment of the present disclosure, the process parameters of the first spraying are: spraying power of 40-70 kW, main gas flow of 50-200 L / min, powder feeding rate of 15-30 g / min, and spraying distance of 8-15 cm.

[0047] In step S102, the main corresponding powder and the doping corresponding powder are mixed mechanically according to a preset ratio to obtain a mixed powder for preparing a gradient ceramic surface layer.

[0048] In one embodiment of the present disclosure, the main phase is one or more of aluminum oxide, zirconium oxide, chromium oxide, yttrium oxide, and hafnium oxide, and the doped phase is one or more of titanium dioxide, silicon carbide, zirconium carbide, chromium carbide, titanium carbide, hafnium carbide, titanium diboride, and zirconium diboride; the mechanical mixing time is 2 to 10 hours, the particle size range of the main phase corresponding to the powder is 25 to 75 μm, and the particle size range of the doped phase corresponding to the powder is 15 to 75 μm.

[0049] The main powder and the doping powder in the gradient ceramic surface layer are mixed in proportion, and then the powders are mechanically mixed and dried for later use.

[0050] In step S103, a second spraying of multiple layers of the mixed powder is continuously performed on the surface of the nickel-based alloy bottom layer to obtain a gradient ceramic surface layer, so as to obtain a gradient antistatic wear-resistant coating composed of the nickel-based alloy bottom layer and the gradient ceramic surface layer.

[0051] Specifically, multiple layers of mixed powder are continuously sprayed on the surface of the nickel-based alloy bottom layer to finally form a gradient ceramic surface layer.

[0052] In one embodiment of the present disclosure, the process parameters of the second spraying are: spraying power of 50-100 kW, main gas flow of 60-200 L / min, powder feeding rate of 15-30 g / min, and spraying distance of 8-15 cm.

[0053] In one embodiment of the present disclosure, the first spraying and the second spraying are both performed by plasma spraying, and the process parameters of the plasma spraying method are: the scanning speed of the plasma generator is 1000-6000 mm / s, the time interval between two deposition cycles in the same coating is 5-60s, and the deposition interval time of each coating in the gradient ceramic surface layer is greater than or equal to 2 minutes.

[0054] Based on the above method, a gradient antistatic wear-resistant coating is prepared. Figure 2 The schematic diagram of the structure of a gradient antistatic wear-resistant coating in an exemplary embodiment of the present disclosure is shown schematically. Figure 3 The macroscopic schematic diagram of a gradient antistatic wear-resistant coating in an exemplary embodiment of the present disclosure is schematically shown. Figure 2 As shown, the coating includes a substrate, a nickel-based alloy bottom layer and a gradient ceramic surface layer.

[0055] Among them, the nickel-based alloy bottom layer is one of nickel-cobalt-chromium-aluminum-yttrium coating, nickel-chromium-aluminum-yttrium coating, cobalt-chromium-aluminum-yttrium coating, nickel-chromium coating, nickel-chromium-aluminum coating, nickel-clad aluminum coating, aluminum-clad nickel coating, and aluminum-clad nickel-chromium coating.

[0056] The gradient ceramic surface layer includes a main phase and a doped conductive phase (doped phase). The main phase is one or more combinations of aluminum oxide, zirconium oxide, chromium oxide, yttrium oxide, and hafnium oxide, and the doped conductive phase is one or more combinations of titanium dioxide, silicon carbide, zirconium carbide, chromium carbide, titanium carbide, hafnium carbide, titanium diboride, and zirconium diboride. The content of the doped phase increases from the inside to the outside, and the mass percentage of the doped phase is 2% to 50%.

[0057] In one embodiment of the present disclosure, the thickness of the nickel-based alloy bottom layer is 50-120 μm, and the porosity is not more than 5%. The thickness of the gradient ceramic surface layer is not more than 500 μm, and the porosity is not more than 5%. The surface resistance of the gradient antistatic wear-resistant coating is 10 6 ~10 8 Ω, bonding strength is greater than or equal to 30MPa, hardness is 900~1500HV 0.3 The average friction coefficient is 0.6~0.9, and the wear rate is (2.0~10.0)×10 -6 mm·N -1 ·m -1 .

[0058] Compared with the prior art, the gradient antistatic wear-resistant coating provided by the present invention has the following advantages:

[0059] (1) Through the coordinated regulation of plasma spraying technology preparation process and coating composition, a multifunctional gradient structure was successfully constructed on the substrate surface. This structural design eliminated the interface between the coatings, effectively relieved the interfacial stress, and enhanced the bonding strength and other properties of the coatings;

[0060] (2) The gradient antistatic wear-resistant coating prepared by the present invention has a uniform and dense structure, high hardness, stable and excellent antistatic and wear-resistant properties, and the static electricity on the coating surface is slowly dissipated along the path formed by the conductive phase inside its gradient structure, thereby avoiding the damage of the substrate to the electrostatic effect, and effectively solving the application limitations of traditional organic coatings in high wear-resistant and antistatic environments;

[0061] (3) The gradient antistatic wear-resistant coating prepared by the present invention has strong applicability and good effect, and can achieve surface strengthening for complex components such as disk rings, shafts, boxes, thin-walled parts, grooves, etc., with good economic and social benefits;

[0062] (4) The gradient antistatic wear-resistant coating preparation method provided by the present invention has a simple and fast operation process, an advanced and reasonable preparation method, and the coating composition and process gradient are precisely controllable, without pollution to the environment. The deposited gradient antistatic wear-resistant coating has high hardness and low wear rate, which effectively extends the service life of parts and components and greatly reduces the waste of resources and energy.

[0063] Example 1

[0064] The gradient antistatic wear-resistant coating of this embodiment is made of the following raw materials in percentage by mass: nickel-based alloy powder is specifically nickel-chromium-aluminum-yttrium powder; in the ceramic powder, the main phase is aluminum oxide, and the doped conductive phase is titanium dioxide.

[0065] The preparation method of the gradient antistatic wear-resistant coating of the present embodiment comprises the following steps:

[0066] Step 1: Clean and dry the substrate for later use;

[0067] Step 2: Alumina powder with a particle size of 25 to 45 μm and doped titanium dioxide powder with a particle size of 15 to 35 μm are mixed in proportion, wherein the mass percentage of titanium dioxide is 2%, 15%, and 35%, respectively, the powders are mechanically mixed for 4 hours, and dried for standby use;

[0068] Step 3: Place the dried substrate in a sandblasting machine for roughening treatment, and then use compressed air to clean the sand on the surface of the substrate;

[0069] Step 4: Prepare a nickel-chromium-aluminum-yttrium coating on the roughened substrate surface by plasma spraying, wherein the nickel-chromium-aluminum-yttrium powder particle size is 45-75μm, and the preparation process parameters are: spraying power is 40kW, main gas flow is 70L / min, powder feeding rate is 15g / min, spraying distance is 12cm, plasma generator sweep speed is 3000mm / s during spraying, coating deposition method is intermittent deposition, and the time interval between two deposition cycles in the same coating is 5s. The thickness of the prepared nickel-chromium-aluminum-yttrium coating is 90μm, and the porosity is 2.0%;

[0070] Step 5: Continuously spray three layers of gradient ceramic surface layer on the surface of the nickel-based alloy bottom layer, in which the content of titanium dioxide is 2%, 15%, and 35% from the inside to the outside of the coating, and the preparation process parameters of the coating are: spraying power is 50kW, main gas flow is 120L / min, powder feeding rate is 25g / min, spraying distance is 12cm, plasma generator sweep speed during spraying is 5000mm / s, and the deposition method of the gradient coating adopts intermittent deposition. The time interval between two deposition cycles in the same coating is 10s, and the deposition interval time of each coating layer is 5min. The thickness of the three layers of gradient ceramic surface layer from the inside to the outside is 100μm, 200μm, and 90μm respectively. The porosity of the gradient ceramic surface layer is 3.3%.

[0071] Figure 4 The cross-sectional view of the gradient antistatic wear-resistant coating prepared by the exemplary embodiment 1 of the present disclosure is schematically shown. Figure 4 As shown, the gradient antistatic wear-resistant coating mainly includes three layers: a substrate, a nickel-based alloy bottom layer and a gradient ceramic surface layer.

[0072] Figure 5 The schematic diagram of the antistatic performance of the gradient antistatic wear-resistant coating prepared in Example 1 of the present disclosure is shown schematically. It shows that the surface resistance of the gradient antistatic wear-resistant coating prepared in Example 1 is 4.0×10 6 Ω, can be regarded as anti-static material, reaching the anti-static level.

[0073] Figure 6 The change curve of the friction coefficient of the gradient antistatic wear-resistant coating prepared by the exemplary embodiment 1 of the present disclosure is schematically shown. The horizontal axis represents the test time (min), and the vertical axis represents the friction coefficient of the gradient antistatic wear-resistant coating. It shows that the average friction coefficient of the gradient antistatic wear-resistant coating prepared in Example 1 is 0.77.

[0074] In summary, the surface resistance of the coating prepared in Example 1 is 4.0×10 6 Ω, bonding strength is 30MPa, hardness is 1260HV 0.3 The average friction coefficient is 0.77 and the wear rate is 4.2×10 -6 mm·N -1 ·m -1 .

[0075] Example 2

[0076] The gradient antistatic wear-resistant coating of this embodiment is made of the following raw materials in percentage by mass: nickel-based alloy powder is specifically nickel-coated aluminum powder; in the ceramic powder, the main phase is zirconium oxide, and the doped conductive phase is zirconium diboride.

[0077] The preparation method of the gradient antistatic wear-resistant coating of the present embodiment comprises the following steps:

[0078] Step 1: Clean and dry the substrate for later use;

[0079] Step 2: Mix zirconium oxide powder with a particle size of 25 to 75 μm and doped zirconium diboride powder with a particle size of 15 to 45 μm in proportion, wherein the mass percentage of zirconium diboride is 10%, 20%, and 25%, respectively, mechanically mix the powder for 6 hours, and dry for standby use;

[0080] Step 3: Place the dried substrate in a sandblasting machine for roughening treatment, and then use compressed air to clean the sand on the surface of the substrate;

[0081] Step 4: A nickel-clad aluminum coating is prepared on the roughened substrate surface by plasma spraying, wherein the nickel-clad aluminum powder particle size is 15-45 μm, and the preparation process parameters are: spraying power is 55 kW, main gas flow is 110 L / min, powder feeding rate is 20 g / min, spraying distance is 15 cm, plasma generator sweep speed during spraying is 5000 mm / s, coating deposition method is intermittent deposition, and the time interval between two deposition cycles in the same coating is 20 s. The thickness of the prepared nickel-clad aluminum coating is 50 μm, and the porosity is 2.5%;

[0082] Step 5: Continuously spray three layers of gradient ceramic surface layer on the surface of the nickel-based alloy bottom layer, in which the content of zirconium diboride is 10%, 20%, and 25% from the inside to the outside of the coating, and the preparation process parameters of the coating are: spraying power is 65kW, main gas flow is 90L / min, powder feeding rate is 30g / min, spraying distance is 8cm, plasma generator sweep speed during spraying is 6000mm / s, and the deposition method of the gradient coating adopts intermittent deposition. The time interval between two deposition cycles in the same coating is 5s, and the deposition interval time of each coating layer is 2min. The thickness of the three layers of gradient ceramic surface layer from the inside to the outside is 150μm, 120μm, and 100μm respectively. The porosity of the gradient ceramic surface layer is 2.6%.

[0083] The surface resistance of the coating prepared in Example 2 was 7.4×10 8 Ω, bonding strength is 42MPa, hardness is 1130HV 0.3 The average friction coefficient is 0.82 and the wear rate is 2.0×10 -6 mm·N -1 ·m -1 .

[0084] Example 3

[0085] The gradient antistatic wear-resistant coating of this embodiment is made of the following raw materials in percentage by mass: nickel-based alloy powder is specifically nickel-chromium-aluminum powder; in the ceramic powder, the main phase is chromium oxide, and the doped conductive phase is titanium dioxide.

[0086] The preparation method of the gradient antistatic wear-resistant coating of the present embodiment comprises the following steps:

[0087] Step 1: Clean and dry the substrate for later use;

[0088] Step 2: Mix chromium oxide with a particle size of 45 to 75 μm and doped titanium dioxide powder with a particle size of 15 to 55 μm in proportion, wherein the mass percentage of titanium dioxide is 10%, 30%, and 50%, respectively, mechanically mix the powder for 4 hours, and dry for standby use;

[0089] Step 3: Place the dried substrate in a sandblasting machine for roughening treatment, and then use compressed air to clean the sand on the surface of the substrate;

[0090] Step 4: Prepare nickel-chromium-aluminum coating on the roughened substrate surface by plasma spraying, wherein the nickel-chromium-aluminum powder particle size is 45-75μm, and the preparation process parameters are: spraying power is 50kW, main gas flow is 50L / min, powder feeding rate is 15g / min, spraying distance is 8cm, plasma generator sweep speed is 1000mm / s during spraying, coating deposition method is intermittent deposition, and the time interval between two deposition cycles in the same coating is 30s. The thickness of the prepared nickel-chromium-aluminum coating is 120μm, and the porosity is 2.7%;

[0091] Step 5: Continuously spray three layers of gradient ceramic surface layer on the surface of the nickel-based alloy bottom layer, in which the content of titanium dioxide is 10%, 30%, and 50% from the inside to the outside of the coating, and the preparation process parameters of the coating are: spraying power is 80kW, main gas flow is 200L / min, powder feeding rate is 25g / min, spraying distance is 15cm, plasma generator sweep speed during spraying is 3000mm / s, and the deposition method of the gradient coating adopts intermittent deposition. The time interval between two deposition cycles in the same coating is 5s, and the deposition interval time of each coating layer is 7min. The thickness of the three layers of gradient ceramic surface layer from the inside to the outside is 100μm, 150μm, and 100μm respectively. The porosity of the gradient ceramic surface layer is 5.0%.

[0092] The surface resistance of the coating prepared in Example 3 was 5.6×10 6 Ω, bonding strength is 33MPa, hardness is 900HV 0.3 The average friction coefficient is 0.90 and the wear rate is 1.0×10 -5 mm·N -1 ·m -1.

[0093] Example 4

[0094] The gradient antistatic wear-resistant coating of this embodiment is made of the following raw materials in percentage by mass: nickel-based alloy powder is specifically nickel-cobalt-chromium-aluminum-yttrium powder; in the ceramic powder, the main phase is zirconium oxide and yttrium oxide, and the doped conductive phase is silicon carbide.

[0095] The preparation method of the gradient antistatic wear-resistant coating of the present embodiment comprises the following steps:

[0096] Step 1: Clean and dry the substrate for later use;

[0097] Step 2: Zirconium oxide and yttrium oxide with a particle size of 25 to 45 μm and doped silicon carbide powder with a particle size of 25 to 45 μm are mixed in proportion, wherein the mass percentage of silicon carbide is 5%, 10%, 15% and 25% respectively, the powders are mechanically mixed for 10 hours, and dried for standby use;

[0098] Step 3: Place the dried substrate in a sandblasting machine for roughening treatment, and then use compressed air to clean the sand on the surface of the substrate;

[0099] Step 4: Prepare a nickel-cobalt-chromium-aluminum-yttrium coating on the roughened substrate surface by plasma spraying, wherein the nickel-cobalt-chromium-aluminum-yttrium powder particle size is 15-75μm, and the preparation process parameters are: spraying power is 65kW, main gas flow is 200L / min, powder feeding rate is 25g / min, spraying distance is 14cm, plasma generator sweep speed during spraying is 4000mm / s, coating deposition method is intermittent deposition, and the time interval between two deposition cycles in the same coating is 60s. The prepared nickel-cobalt-chromium-aluminum-yttrium coating has a thickness of 100μm and a porosity of 2.3%;

[0100] Step 5: Continuously spray four layers of gradient ceramic surface layer on the surface of the nickel-based alloy bottom layer, wherein the content of silicon carbide is 5%, 10%, 15%, and 25% from the inside to the outside of the coating, and the preparation process parameters of the coating are: spraying power is 57kW, main gas flow is 60L / min, powder feeding rate is 10g / min, spraying distance is 15cm, plasma generator sweep speed during spraying is 1000mm / s, and the deposition method of the gradient coating adopts intermittent deposition. The time interval between two deposition cycles in the same coating is 60s, and the deposition interval time of each coating layer is 5min. The thickness of the four layers of gradient ceramic surface layer from the inside to the outside is 50μm, 100μm, 50μm, and 100μm. The porosity of the gradient ceramic surface layer is 3.5%.

[0101] The surface resistance of the coating prepared in Example 4 was 1.3×10 7Ω, bonding strength is 37MPa, hardness is 1390HV 0.3 The average friction coefficient is 0.75 and the wear rate is 5.3×10 -6 mm·N -1 ·m -1 .

[0102] Example 5

[0103] The gradient antistatic wear-resistant coating of this embodiment is made of the following raw materials in percentage by mass: nickel-based alloy powder is specifically nickel-chromium powder; in the ceramic powder, the main phase is aluminum oxide and chromium oxide, and the doped conductive phase is titanium diboride.

[0104] The preparation method of the gradient antistatic wear-resistant coating of the present embodiment comprises the following steps:

[0105] Step 1: Clean and dry the substrate for later use;

[0106] Step 2: Aluminum oxide and chromium oxide with a particle size of 45 to 75 μm and doped titanium diboride powder with a particle size of 45 to 75 μm are mixed in proportion, wherein the mass percentage of titanium diboride is 5%, 15%, and 25%, respectively, the powders are mechanically mixed for 2 hours, and dried for standby use;

[0107] Step 3: Place the dried substrate in a sandblasting machine for roughening treatment, and then use compressed air to clean the sand on the surface of the substrate;

[0108] Step 4: A nickel-chromium coating is prepared on the roughened substrate surface by plasma spraying, wherein the nickel-chromium powder particle size is 45-75 μm, and the preparation process parameters are: spraying power is 70 kW, main gas flow is 130 L / min, powder feeding rate is 30 g / min, spraying distance is 12 cm, plasma generator sweep speed during spraying is 6000 mm / s, coating deposition method is intermittent deposition, and the time interval between two deposition cycles in the same coating is 15 s. The thickness of the prepared nickel-chromium coating is 90 μm, and the porosity is 5.0%;

[0109] Step 5: Continuously spray three layers of gradient ceramic surface layer on the surface of the nickel-based alloy bottom layer, wherein the content of titanium diboride is 5%, 15%, and 25% from the inside to the outside of the coating, and the preparation process parameters of the coating are: spraying power is 100kW, main gas flow is 130L / min, powder feeding rate is 20g / min, spraying distance is 12cm, plasma generator sweep speed during spraying is 4000mm / s, gradient coating deposition method adopts intermittent deposition, the time interval between two deposition cycles in the same coating is 35s, and the deposition interval time of each coating layer is 6min. The thickness of the three layers of gradient ceramic surface layer from the inside to the outside is 150μm, 150μm, and 100μm. The porosity of the gradient ceramic surface layer is 3.0%.

[0110] The surface resistance of the coating prepared in Example 5 was 6.7×10 6 Ω, bonding strength is 31MPa, hardness is 1500HV 0.3 The average friction coefficient is 0.60 and the wear rate is 3.7×10 -6 mm·N -1 ·m -1 .

[0111] Comparative Example 1

[0112] The coating consists of a nickel-chromium-aluminum-yttrium bottom layer and a pure aluminum oxide surface layer. The thickness of the pure aluminum oxide surface layer is 390 μm. The rest of the process is the same as in Example 1.

[0113] The surface resistance of the coating prepared in Comparative Example 1 was 8.2×10 10 Ω, bonding strength is 28MPa, hardness is 1330HV 0.3 The average friction coefficient is 0.75 and the wear rate is 3.8×10 -6 mm·N -1 ·m -1 .

[0114] Comparative Example 2

[0115] The coating is composed of a nickel-chromium-aluminum-yttrium bottom layer and a ceramic surface layer. The main phase of the ceramic surface layer is aluminum oxide, the doping phase is titanium dioxide, the content of titanium dioxide is 35%, the thickness of the ceramic surface layer is 390 μm, and the rest of the process is the same as in Example 1.

[0116] The surface resistance of the coating prepared in Comparative Example 2 was 7.3×10 5 Ω, bonding strength is 30MPa, hardness is 1260HV 0.3 The average friction coefficient is 0.77 and the wear rate is 4.2×10 -6 mm·N -1 ·m -1 .

[0117] Comparative Example 3

[0118] The coating is composed of a nickel-chromium-aluminum-yttrium bottom layer and a ceramic surface layer. The ceramic surface layer is composed of aluminum oxide and titanium dioxide, and the content of titanium dioxide is 60%, 70%, and 80% from the inner side to the outer side of the coating. The thickness of the ceramic surface layer is 390 μm, and the rest of the process is the same as in Example 1.

[0119] The surface resistance of the coating prepared in Comparative Example 3 was 2.1×10 5 Ω, bonding strength is 33MPa, hardness is 750HV 0.3 The average friction coefficient is 0.85 and the wear rate is 7.6×10 -6 mm·N -1 ·m -1 .

[0120] Comparative Example 4

[0121] The coating is composed of a nickel-chromium-aluminum-yttrium bottom layer and a ceramic surface layer. The ceramic surface layer is composed of alumina and aluminum, and the content of aluminum is 2%, 15%, and 35% from the inner side to the outer side of the coating. The thickness of the ceramic surface layer is 390 μm, and the rest of the process is the same as in Example 1.

[0122] The surface resistance of the coating prepared in Comparative Example 4 was 1.1×10 6 Ω, bonding strength is 32MPa, hardness is 420HV 0.3 The average friction coefficient is 0.94 and the wear rate is 6.3×10 -4 mm·N -1 ·m -1 .

[0123] The surface resistance, bonding strength, hardness, friction coefficient and wear rate of the coating were tested for the above embodiments and comparative examples. The results are shown in Table 1:

[0124] Table 1

[0125]

[0126] As can be seen from Table 1, compared with Examples 1 to 5, Comparative Examples 1 to 4 respectively provide the implementation effects of different coating components, structures and contents. From the test results, it can be seen that the surface resistance of Comparative Examples 1 to 3 is not within 10 6 Up to 10 8 Ω range, indicating that the coating cannot achieve antistatic effect. 6 Up to 10 8 Within the Ω range, the anti-static level is achieved, but its wear resistance is seriously deteriorated.

[0127] Taking Example 1 as an example, it can be seen from the comparison between Example 1 and Comparative Example 1 that the surface layer provided in Example 1 is a titanium dioxide doped aluminum oxide coating, wherein the doping amount of titanium dioxide is 2%, 15%, and 35% respectively, while the surface layer provided in Comparative Example 1 is a pure aluminum oxide coating. The surface resistance of the coating obtained in Comparative Example 1 is 8.2×10 10 Ω, much higher than Example 1, and the antistatic effect is not achieved. This is because the resistance of pure alumina is very high, and the static charge accumulated on the coating surface cannot be effectively channeled, which poses a great safety hazard. The titanium dioxide doped in Example 1 is conductive, and the titanium dioxide phase in the gradient coating forms a conductive channel, which effectively channels the static electricity accumulation on the coating surface. The test results of Example 1 and Comparative Example 1 illustrate the necessity of doping the conductive phase in the ceramic surface layer in the present invention in the field of antistatic.

[0128] By comparing Example 1 with Comparative Example 2, it can be seen that the surface layer of Example 1 is a titanium dioxide doped aluminum oxide coating, wherein the doping amount of titanium dioxide is 2%, 15%, and 35% respectively, while the surface layer of Comparative Example 1 is a titanium dioxide doped aluminum oxide coating, and the content of titanium dioxide is 35%. The surface resistance of the coating obtained in Comparative Example 2 is 7.3×10 5 Ω, which is lower than that of Example 1, and the antistatic effect is not achieved. This is because the conductivity of titanium dioxide enables the ceramic surface layer to have the ability to conduct current, and the static electricity dissipates too quickly, which is very easy to break through the substrate. It is not suitable for electronic components, power stations, electric shocks and other places that are susceptible to discharge damage. The test results of Example 1 and Comparative Example 2 illustrate the advantages of the gradient coating in the field of antistatic in the present invention.

[0129] By comparing Example 1 with Comparative Example 3, it can be seen that the surface layer of Example 1 is a titanium dioxide doped aluminum oxide coating, wherein the doping amount of titanium dioxide is 2%, 15%, and 35% respectively, while the surface layer of Comparative Example 3 is a titanium dioxide doped aluminum oxide coating, wherein the content of titanium dioxide is 60%, 70%, and 80% respectively. Both Example 1 and Comparative Example 3 have gradient structures, and the surface resistance of the coating obtained in Comparative Example 3 is 2.1×10 5 Ω, which is much lower than that of Example 1, and the antistatic effect is not achieved, and the hardness and wear resistance of the coating in Comparative Example 3 are seriously deteriorated. The test results of Example 1 and Comparative Example 3 show that the content of the conductive phase in the gradient coating of the present invention is one of the important factors affecting the performance of the coating, and the content of the conductive phase in the gradient coating needs to be controlled to give full play to its antistatic performance. In other words, the scheme of the embodiment of the present disclosure can improve the comprehensive performance of the coating, and the coating performance can be controlled by adjusting the coating components and process parameters.

[0130] By comparing Example 1 with Comparative Example 4, it can be seen that the surface layer of Example 1 is a titanium dioxide doped aluminum oxide coating, wherein the doping amount of titanium dioxide is 2%, 15%, and 35% in sequence, while the surface layer of Comparative Example 4 is an aluminum doped aluminum oxide coating, wherein the content of aluminum is 2%, 15%, and 35% in sequence. Both Example 1 and Comparative Example 4 have gradient structures, and the content of doped phase is the same. The surface resistance of the coating obtained in Comparative Example 4 is 1.1×10 6 Ω, achieving an anti-static effect. However, the hardness and wear resistance of the coating in Comparative Example 4 are seriously deteriorated. This is because aluminum has good electrical conductivity, and an appropriate amount of aluminum doped into alumina ceramics can make the material reach an anti-static level, but aluminum, as a metal, has a much lower hardness than ceramics and poor wear resistance. It cannot be used for a long time in an environment with high requirements for wear resistance and anti-static performance. The test results of Example 1 and Comparative Example 4 show that the composition of the conductive phase in the gradient coating of the present invention is also one of the important factors affecting the performance of the coating. Only by doping with specific components can the simultaneous improvement of anti-static performance and wear resistance be achieved. In other words, the scheme of the embodiment of the present disclosure can improve the comprehensive performance of the coating, and the coating performance can be controlled by adjusting the coating components and process parameters.

[0131] It should be noted that although the steps of the method in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.

[0132] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0133] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure.

[0134] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A method for preparing a gradient antistatic wear-resistant coating, characterized in that: include: The substrate is roughened, and a nickel-based alloy powder is first sprayed on the surface of the roughened substrate to obtain a nickel-based alloy bottom layer; The main corresponding powder and the doping corresponding powder are mixed mechanically according to a preset ratio to obtain a mixed powder for preparing a gradient ceramic surface layer; A second spraying of multiple layers of the mixed powder is continuously performed on the surface of the nickel-based alloy bottom layer to obtain a gradient ceramic surface layer, so as to obtain a gradient antistatic wear-resistant coating composed of the nickel-based alloy bottom layer and the gradient ceramic surface layer.

2. The method for preparing the gradient antistatic wear-resistant coating according to claim 1, characterized in that: The nickel-based alloy bottom layer is one of nickel-cobalt-chromium-aluminum-yttrium coating, nickel-chromium-aluminum-yttrium coating, cobalt-chromium-aluminum-yttrium coating, nickel-chromium coating, nickel-chromium-aluminum coating, nickel-clad aluminum coating, aluminum-clad nickel coating, and aluminum-clad nickel-chromium coating; the particle size range of the nickel-based alloy powder is 15 to 75 μm.

3. The method for preparing the gradient antistatic wear-resistant coating according to claim 1, characterized in that: The process parameters of the first spraying are: spraying power of 40-70 kW, main gas flow of 50-200 L / min, powder feeding rate of 15-30 g / min, and spraying distance of 8-15 cm.

4. The method for preparing the gradient antistatic wear-resistant coating according to claim 1, characterized in that: The main phase is one or more of aluminum oxide, zirconium oxide, chromium oxide, yttrium oxide, and hafnium oxide, and the doped phase is one or more of titanium dioxide, silicon carbide, zirconium carbide, chromium carbide, titanium carbide, hafnium carbide, titanium diboride, and zirconium diboride; the mechanical mixing time is 2 to 10 hours, the particle size range of the main phase corresponding powder is 25 to 75 μm, and the particle size range of the doped phase corresponding powder is 15 to 75 μm.

5. The method for preparing the gradient antistatic wear-resistant coating according to claim 1, characterized in that: The process parameters of the second spraying are: spraying power of 50-100 kW, main gas flow of 60-200 L / min, powder feeding rate of 15-30 g / min, and spraying distance of 8-15 cm.

6. The method for preparing the gradient antistatic wear-resistant coating according to claim 1, characterized in that: The first spraying and the second spraying are both carried out by plasma spraying, and the process parameters of the plasma spraying method are: the scanning speed of the plasma generator is 1000-6000mm / s, the time interval between two deposition cycles in the same coating is 5-60s, and the deposition interval time of each coating in the gradient ceramic surface layer is greater than or equal to 2min.

7. A gradient antistatic wear-resistant coating, characterized in that: The gradient antistatic wear-resistant coating is obtained by the preparation method of the gradient antistatic wear-resistant coating as described in claims 1 to 6 above, and the gradient antistatic wear-resistant coating comprises: A nickel-based alloy bottom layer and a gradient ceramic surface layer, wherein the gradient ceramic surface layer comprises a main phase and a doped phase; the content of the doped phase increases from the inside to the outside, and the mass percentage of the doped phase is 2% to 50%.

8. The gradient antistatic wear-resistant coating according to claim 7, characterized in that: The thickness of the nickel-based alloy bottom layer is 50-120 μm, and the porosity does not exceed 5%.

9. The gradient antistatic wear-resistant coating according to claim 7, characterized in that: The thickness of the gradient ceramic surface layer does not exceed 500 μm, and the porosity does not exceed 5%.

10. The gradient antistatic wear-resistant coating according to claim 7, characterized in that: The surface resistance of the gradient antistatic wear-resistant coating is 10 6 ~10 8 Ω, bonding strength is greater than or equal to 30MPa, hardness is 900~1500HV 0.3 The average friction coefficient is 0.6~0.9, and the wear rate is (2.0~10.0)×10 -6 mm·N -1 ·m -1 .

Citation Information

Cited By

  • Ceramic coating and preparation method thereof

    CN121228153A